Menasseh ben Israel: Rabbi of Amsterdam - Nadler, Steven M. (Jewish Lives, 2018)
Cover -- Half Title -- Title -- Dedication -- Copyright -- Contents -- 1. Prologue: On the Houtgracht -- 2. Manoel/Menasseh -- 3. On the Nieuwe Houtmarkt -- 4. The Conciliator -- 5. "I am not my own master -- 6. The Hope of Israel -- 7. The English Mission -- 8. Denouement -- Appendix: Menasseh ben Israel and Rembrandt -- Acknowledgments -- Notes -- Bibliography -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z